1999
DOI: 10.1210/jc.84.2.670
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Suppression of Insulin Secretion and Gene Expression in Human Pancreatic Islets: Implications for the Development of Adipogenic Diabetes Mellitus

Abstract: Previously we demonstrated the expression of the long form of the leptin receptor in rodent pancreatic β-cells and an inhibition of insulin secretion by leptin via activation of ATP-sensitive potassium channels. Here we examine pancreatic islets isolated from pancreata of human donors for their responses to leptin. The presence of leptin receptors on islet β-cells was demonstrated by double fluorescence confocal microscopy after binding of a fluorescent derivative of human leptin (Cy3-leptin). Leptin (6.25 nM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
5
9

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(202 citation statements)
references
References 36 publications
9
179
5
9
Order By: Relevance
“…This is important, since, based on the inhibitory effects of leptin on insulin secretion in vitro, it has been proposed that the failure of leptin to inhibit insulin secretion from the b-cells of obaob mice may explain in part the development of hyperinsulinemia, insulin resistance and the progression to diabetes. 10,26 In agreement with the present data, it has been suggested that the long-term normalization of glucose tolerance in leptin gene treated obaob mice was not solely related to increased insulin sensitivity, but also due to improved insulin secretion. 7 We also show that leptin treatment decreased islet G6Pase activity.…”
Section: Insulin Release In Obaob Mouse Islets a Khan Et Alsupporting
confidence: 92%
See 1 more Smart Citation
“…This is important, since, based on the inhibitory effects of leptin on insulin secretion in vitro, it has been proposed that the failure of leptin to inhibit insulin secretion from the b-cells of obaob mice may explain in part the development of hyperinsulinemia, insulin resistance and the progression to diabetes. 10,26 In agreement with the present data, it has been suggested that the long-term normalization of glucose tolerance in leptin gene treated obaob mice was not solely related to increased insulin sensitivity, but also due to improved insulin secretion. 7 We also show that leptin treatment decreased islet G6Pase activity.…”
Section: Insulin Release In Obaob Mouse Islets a Khan Et Alsupporting
confidence: 92%
“…In accordance with this, leptin treatment in vitro has been shown to inhibit GSIS in islets from obaob and lean mice, 9,10 normal rats 24,25 and humans. 26,27 In other studies, leptin was without any effect on GSIS. 12,13 These differences are most probably due to different experimental conditions, the dose or source of leptin, the duration of the leptin treatment and the lack of bioactivity of some preparations of leptin that have been used.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have shown leptin to decrease basal insulin secretion from the pancreatic islets 34 and down-regulates insulin gene transcription. 35 Leptin receptors have been demonstrated on the β-pancreatic cell, 36 and in animal studies acute physiologic increases in leptin significantly inhibited glucose stimulated insulin secretion in a dose-dependent manner. 37 Plasma levels of leptin, adequate to significantly suppress insulin, are found in mild obesity 38 and patients with IGT.…”
Section: Neuropeptides and Impaired Glucose Tolerancementioning
confidence: 99%
“…Suppression of insulin secretion and gene transcription by leptin in the obese range has also been demonstrated in human pancreatic islets. 15,17 It should be noted, however, that not all studies have reported inhibitory effects of leptin on insulin secretion. Thus, Shimizu et al, 24 and Tanizawa et al, 25 have actually shown stimulation of insulin secretion by leptin at a physiological range of concentrations, in HIT-T15 and MIN-6 cells, respectively.…”
Section: Inhibition Of Insulin Transcription By Tnfa and Leptinmentioning
confidence: 99%
“…15 ± 18 Moreover, leptin suppressed glucose or GLP-1 induced proinsulin gene transcription in isolated islets and b pancreatic cells. 17,19,20 In obaob mice, the animal model of obesity showing metabolic abnormalities similar to those seen in obese type 2 diabetic humans, daily administration of leptin could lower serum insulin and glucose levels, independently of its weight reducing effect. 21,22 Other studies, however, have either failed to show any effect on insulin release from isolated rat pancreases, 23 or have shown a stimulatory effect of leptin on basal but not glucose-stimulated insulin secretion and biosynthesis in pancreatic b cells.…”
Section: Introductionmentioning
confidence: 99%